ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SD INPRES MAPUNG KABUPATEN GOWA - Sudarto Sudarto; Muhammad Amin; Muh. Arfah Anwar (JOEL: Journal of Educational and Language Research, 2023)
This research is a descriptive qualitative research that aims to describe the teacher's pedagogic competence in improving the science learning outcomes at SD Inpres Mapung, Gowa Regency. The subjects in this study were the Fourth Grade teacher at SD Inpres Mapung, Gowa Regency. The research data were obtained through observation sheets and interview guidelines. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Research results: yhe teacher is able to design the lessons in the form of lesson plans and apply them according to K13, carry out the learning activities according to K13, use a variety of learning methods and media according to student characteristics, able to evaluate learning outcomes in general according to K13. Factors influencing teacher pedagogical competence in improving student science learning outcomes are teachers participating in teacher training or seminars interacting with students and with students' parents. Conclusion: in general, teachers have been had pedagogical competence according to predetermined indicators